ANALISIS SEMIOTIKA KONSEP DIRI PADA FILM PENDEK “CHANGED” - Azwar Munanjar; Nina Kusumawati (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
Short film “Changed” tells of a man named Leo who is not confident, he is supported in a woman's soul so that he behaves and looks like a woman. He did everything he could to have an ideal and perfect body. This short film gives a message that has certain meanings, including the self-concept of the character. The message is visible on the sign that is on the scene and dialog in the image. The author in this study used a qualitative method with the assessment of semiotic analysis from Charles Sanders Peirce. In this study we will look for answers to the question of how to self-concept in the search for the identity of the character through verbal and nonverbal messages. The results of the overall research come to our picture and self-assessment of the character's secret that is trapped in a woman's body image, the ideal of the body as a woman, her role as a woman and her identity known as a woman trapped in a man's body Keywords: Short Movie, Semiotics, Charles Sanders Pierce, self-concept